THE EFFECT OF FOREIGN DIRECT INVESTMENT ON INDONESIAâS STOCK MARKET PERFORMANCE - Anggara Gunawan, Kris
This study investigates the effect of foreign direct investment (FDI) on Indonesia’s stock market performance. An estimating equation model applies to the time series data covering Indonesia from 1995 to 2019. The results of the study shows that key variables such as FDI has positive relationship on stock market performance due to the surge of FDI inflows into country contributes to increase economic growth and leads also to an increase in stock market index. This study also finds that exchange rate and stock traded has positively correlation with Indonesia’s stock performance, while trade openness has a negative effect on stock performance.